2022
DOI: 10.3389/fpsyt.2021.753800
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of Mental Health Status Among Police Recruits in Sweden

Abstract: BackgroundThe stressful and complex nature of police work and its adverse effects on mental health are well-documented in police research. The mental health of police students however, has not been given the same attention. To the best of our knowledge, studies on the mental health of Swedish police recruits have not been undertaken since 2010.ObjectivesThe present study aims to examine whether there are differences in the mental health between two cohorts (2009 and 2020) of Swedish police recruits, as well as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…A study of the mental health of police apprentices in Sweden found that they were mentally much healthier than the general population. In terms of personality, Harm Avoidance and Self Directedness were found to be associated with all aspects of psychopathology, as well as good mental health and mature personality traits, with women reporting more of these traits [ 19 ]. In the other Swedish study, police recruits self-reported being happier, less anxious, less aggressive, and less impulsive than civilians; less sensitive to reinforcement, whether in terms of punishment or reward; and more socially desirable [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study of the mental health of police apprentices in Sweden found that they were mentally much healthier than the general population. In terms of personality, Harm Avoidance and Self Directedness were found to be associated with all aspects of psychopathology, as well as good mental health and mature personality traits, with women reporting more of these traits [ 19 ]. In the other Swedish study, police recruits self-reported being happier, less anxious, less aggressive, and less impulsive than civilians; less sensitive to reinforcement, whether in terms of punishment or reward; and more socially desirable [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…The police academy is vital for a police career, providing skills, knowledge, and preparation for challenges [ 18 , 19 ]. The COVID-19 pandemic exposed deficiencies in digital readiness, equipment, and infrastructure for police training, revealing numerous challenges ahead [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Police officers are generally considered to be a high-risk group for the development of psychological illnesses due to the numerous significant and potentially traumatic events they experience during their careers. 3,4 The duties and responsibilities in police officers place them in difficult and stressful circumstances, which can have a major consequence on their mental health and probably even performance. 5 Previous research has linked law enforcement work to higher levels of physical, psychosocial, and anticipatory stress.…”
Section: Introductionmentioning
confidence: 99%